Does cardiorespiratory fitness protect memory from sleep deprivation? - Ayotte, Beatrice; Cristini, Jacopo; Lotlikar, Madhura; Parwanta, Zohra; Cossette, Philippe; Gasparovic, Leah; Yee-Wong, Meghan; He, Qi Yue; Doyon, Julien; Dal Maso, Fabien; Carrier, Julie; Steib, Simon; et al. (Medicine and science in sports and exercise, 2023)
INTRODUCTION: Animal studies have demonstrated that physical exercise can protect memory from the effects of sleep deprivation (SD). We examined whether having a high cardiorespiratory fitness (V̇O 2peak ) is associated with an enhanced capacity to encode episodic memory after one night of SD. METHODS: Twenty-nine healthy young participants were allocated into either an SD group ( n = 19) that underwent 30 h of uninterrupted wakefulness, or a sleep control (SC) group ( n = 10) that followed a regular sleep routine. Following either the SD or SC period, participants were asked to view 150 images as the encoding part of the episodic memory task. Ninety-six hours after viewing the images, participants returned to the laboratory to perform the recognition part of the episodic memory task, which required the visual discrimination of the 150 images previously presented from 75 new images introduced as distractors. Cardiorespiratory fitness (V̇O 2peak ) was assessed with a bike ergometer graded exercise test. Group differences in memory performance were assessed with independent t tests and associations between V̇O 2peak and memory with multiple linear regression. RESULTS: The SD group showed a significant increase in subjective fatigue (mean difference [MD] [standard error SE] = 38.94 [8.82]; P = 0.0001) and a worse capacity to identify the original 150 images (MD [SE] = -0.18 [0.06]; P = 0.005) and discriminate them from distractors (MD [SE] = -0.78 [0.21] P = 0.001). When adjusted for fatigue, higher V̇O 2peak was significantly associated with better memory scores in the SD (R 2 = 0.41; β [SE] = 0.03 [0.01]; P = 0.015) but not in the SC group ( R2 = 0.23; β [SE] = 0.02 [0.03]; P = 0.408). CONCLUSIONS: These results confirm that SD before encoding impairs the capacity to create robust episodic memories and provide preliminary support to the hypothesis that maintaining high levels of cardiorespiratory fitness could have a protective effect against the disruptive effects of sleep loss on memory.
Gesehen am 25.10.2023